2012
DOI: 10.14207/ejsd.2012.v1n2p199
|View full text |Cite
|
Sign up to set email alerts
|

Food Security in Nigeria: An Overview

Abstract: No doubt, food is life; hence, food has become an instrument of national power. It is within that imperatival need for food that this paper takes a cursory look at the issue in all its ramifications. The paper with a comprehensive review of Nigeria's agricultural policy noted that much still needs to be done if the crisis in the sector will not escalate more so, in a supposedly democratic dispensation which expectedly should promote the value of welfarism. The paper infers that Nigeria needs to come up with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…Several studies have investigated the challenge of food security in Nigeria. Adebayo et al [10] identified inadequate funding and government overdependence on oil as the leading causes of food insecurity. The authors warned that developed countries might use food as an instrument of exploitation in the future and recommended biotechnology adoption to solve food security challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the challenge of food security in Nigeria. Adebayo et al [10] identified inadequate funding and government overdependence on oil as the leading causes of food insecurity. The authors warned that developed countries might use food as an instrument of exploitation in the future and recommended biotechnology adoption to solve food security challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Food Consumption pattern in Nigeria Youth Farm Lab (YFL): This is an initiative of the Federal government of Nigeria (FMARD10 ) and Synergos11 to educate young Nigerians in the development of livestock and sustainable urban agriculture. YFL searches for Nigerians between the ages of 18 and 35 who are excited about agriculture and believe in itsThe federal government of Nigeria earmarks ₦169.88 billion on road construction in 202012 .…”
mentioning
confidence: 99%
“…Likewise in Nigeria, where the agricultural sector as the most important non-oil economic activity employs 70% of labor forces and contributes 40.07% of GDP (NBS, 2010). The sector up to the 1960s was the main pillar of the Nigerian economy providing enough food to the citizens and at the same time export the surplus food items to the foreign market, for instance; the famous groundnut pyramids in the Kano in the North, cocoa in the west, oil palm and kernel heaps in the East, and the rubber plantation in the Mid-west asserts the notion (Adebayo & Ojo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Northeast and some parts of the northcentral parts of Nigeria have been characterised by chronic food insecurity driven by the clashes between local farmers and cattle herders (World Food Programme, 2019), low-level of food production (FAO et al, 2018) relative to population growth (UN DESA, 2019). Food production in Nigeria has faced severe obstacles, such as adverse climate shocks, unpredictable rainfall (Adebayo & Ojo, 2012), lack of modern farm inputs and technologies, government neglect and lack of policy directions (Verter, 2016;MBNP, 2017;FAO el at., 2018). These constraints, coupled with other impediments, have nullified Nigeria's capacity to achieve food self-sufficiency (UNCTAD, 2019;FSIN, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These constraints, coupled with other impediments, have nullified Nigeria's capacity to achieve food self-sufficiency (UNCTAD, 2019;FSIN, 2019). Consequently, Nigeria has substantially dependent on advanced and emerging economies for processed food products (Adebayo & Ojo, 2012), as postulated by dependency theories (Verter, 2016). Free trade in food trade and over-reliant on food imports have been arguably accused of being among the principal causes of undernutrition and food insecurity in developing countries.…”
Section: Introductionmentioning
confidence: 99%